Nanger, Eudorcas, Gazella, and Antilope form a well-supported chromosomal clade within Antilopini (Bovidae, Cetartiodactyla) - Cernohorska, Halina; Kubickova, Svatava; Kopecna, Olga; Vozdova, Miluse; Matthee, Conrad A; Robinson, Terence J; Rubes, Jiri (Chromosoma, 2015)
The evolutionary clade comprising Nanger, Eudorcas, Gazella, and Antilope, defined by an X;BTA5 translocation, is noteworthy for the many autosomal Robertsonian fusions that have driven the chromosome number variation from 2n = 30 observed in Antilope cervicapra, to the 2n = 58 in present Eudorcas thomsoni and Eudorcas rufifrons. This work reports the phylogenetic relationships within the Antilopini using comprehensive cytogenetic data from A. cervicapra, Gazella leptoceros, Nanger dama ruficollis, and E. thomsoni together with corrected karyotypic data from an additional nine species previously reported in the literature. Fluorescence in situ hybridization using BAC and microdissected cattle painting probes, in conjunction with differential staining techniques, provide the following: (i) a detailed analysis of the E. thomsoni chromosomes, (ii) the identification and fine-scale analysis the BTA3 orthologue in species of Antilopini, and (iii) the location of the pseudoautosomal regions on sex chromosomes of the four species. Our phylogenetic analysis of the chromosomal data supports monophyly of Nanger and Eudorcas and suggests an affiliation between A. cervicapra and some of the Gazella species. This renders Gazella paraphyletic and emphasizes a closer relationship between Antilope and Gazella than what has previously been considered.
Keywords: Gene Rearrangement; skot; Karyotyping; savčí chromozomy; klonování DNA; Biological Evolution; Chromosome Painting; Female; translokace genetická; satelitní DNA; karyotypizace; centromera; molekulární evoluce; Male; DNA, Satellite; ženské pohlaví; antilopy; Phylogeny; In Situ Hybridization, Fluorescence; biologická evoluce; genová přestavba; Cloning, Molecular; hybridizace in situ fluorescenční; pohlavní chromozomy; Centromere; fylogeneze; mužské pohlaví; Antelopes; Chromosomes, Mammalian; Animals; Evolution, Molecular; malování chromozomů; Cattle; Sex Chromosomes; zvířata; Translocation, Genetic